Rediscovery of the Pallid Shiner, Hybopsis amnis, in the Black River System of Arkansas and Missouri Including Notes on Ecology and Life History - Daniel P Morrill; Calvin R Rezac; Ginny Adams; S. R. Adams; Robert Hrabik (Southeastern Fishes Council Proceedings, 2021)
The Pallid Shiner, Hybopsis amnis, is a rare and understudied minnow with little information about its ecology. This species is listed as a Species of Greatest Conservation Need (SGCN) throughout much of its range and is generally considered to be declining. It had not been detected in the Black River system of Missouri and Arkansas in over 75 years, or the state of Missouri in over 60 years. We sampled over 100 sites in the Black River system between 2017 and 2020 to assess temporal trends in fish assemblage structure and to update the status of SGCN species in this drainage. We collected 226 H. amnis at seven different sites in the Black River system. We measured total lengths to estimate age classes and year of spawning. Corresponding habitat and year class data indicate this species may spawn in late winter to early spring and rely on floodplain habitat for spawning and recruitment. The apparent decline of H. amnis in other systems may be a result of reduced floodplain connectivity.